Chefs’ Attitudes and Sensory Analysis of Invasive Crayfish (Faxonius limosus) Meat: Psychological and Culinary Aspects - Maja Paunić; Jasmina Lazarević; Dubravka Škrobot; Ivana Čabarkapa; Stefan Šmugović; Milica Vidosavljević; Miloš Županjac (Foods)
Considering the growing significance of sustainable gastronomy and the need for controlling the populations of invasive species, the aim of this study is to explore chefs’ attitudes toward the sensory and psychological aspects of using invasive crayfish meat (Faxonius limosus) from the Danube. The study was conducted using a survey questionnaire with a sample of 210 respondents, employing a consumption restriction scale based on various psychological aversions to non-traditional food sources. Binary logistic regression indicated a significant impact of psychological aversion on the likelihood of accepting this raw material. Thirty chefs participated in the sensory evaluation of the crayfish meat. The results revealed that the meat has potential for broad application in the preparation of gastronomic products.